The Sibling Effect for Delinquency: Mediation by Proactive Criminal Thinking and Moderation by Age - Walters, Glenn D. (International journal of offender therapy and comparative criminology, 2020)
This study tested whether the sibling delinquency effect, like the peer influence effect, is mediated by proactive (planned, calculated, and amoral) criminal thinking. Youth who completed the Offending, Crime and Justice Survey (OCJS) and had a sibling living at home were divided into an early adolescent subsample (n = 795) and a mid-adolescent subsample (n = 532) after it was determined that age moderated the effect of sibling delinquency on proactive criminal thinking and serious offending. The results of a causal mediation analysis revealed a significant pathway running from sibling delinquency at Wave 1, to proactive criminal thinking at Wave 2, to serious offending at Wave 3, but only in the early adolescent subsample. These results suggest that the sibling delinquency effect may be the result of learning proactive criminal thinking in association with a delinquent sibling while still an early adolescent.